FAKTOR-FAKTOR YANG MEMPENGARUHI MUZAKI MEMBAYAR DAN TIDAK MEMBAYAR ZAKAT PADA LAZISMU KABUPATEN JEMBER - Al Ghofiqi, Munadzir Ahsan (Universitas Muhammadiyah Jember, 2018)
This research focuses on factors that influence muzaki in whether they pay zakat or not to LAZISMU Jember. It aims to reveal each variable which influences and distunguish it significantly. The variables used are organisation, knowledge and understanding on the applied rules and good zakat governance. The object of this research is muzaki who pay and who do not pay zakat to LAZISMU Jember. The respondents of this research are 60 muzaki and the research was done in a month. The result of data analysis using discriminant analysis reveals that there is significant difference. The significant difference is based on F Test to variable knowledge and understanding on the applied rules and good zakat governance. Both variables influence and distunguish significantly to muzaki in whether they pay zakat or not to LAZISMU Jember.While the organisation variables can?t be included in the discriminant model because of that variables are not able to distinguish muzaki pay zakat or not to LAZISMU Jember. Thus, variable organisation does not influence and distingush significantly to muzaki whether they pay zakat or not to LAZISMU Jember.